Nowoczesna oczyszczalnia ścieków w gminie Łagów Lubuski - pierwsze miesiące eksploatacji = The modern wastewater treatment plant in Lagow community - first months of the operation - Sadecka, Zofia; Myszograj, Sylwia; Sieciechowicz, Aleksandra; Suchowska-Kisielewicz, Monika; Waś, Janusz; Musiałowicz, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The choice of technology, particularly in the case of small objects should provide a highly effective wastewater treatment with the removal of nitrogen and phosphorus. The paper shows that the new wastewater treatment for community Lagow Lubuski, allows to achieved parameters in treated wastewater below the required given in the regulation of the Minister of the Environment (Journal of Laws of 2006, No. 137, item 984). High efficiency of removal of nutrients can be obtained with energy consumption of 0.4 kWh per 1 m3 of sewage.
Keywords: oczyszczalnia ścieków; usuwanie związków biogennych; wastewater treatment plant; removal of nutrients